2015
DOI: 10.1007/s10725-015-0065-7
|View full text |Cite
|
Sign up to set email alerts
|

Breaking seed dormancy of Alliaria petiolata with phytohormones

Abstract: The leaves of Alliaria petiolata have a potential to be used as green salad due to garlic like fragrance and high value of vitamin C and A. Unfortunately, it exhibited deprived germination because of poor physiological impediment and seed dormancy. In order to improve germination, scarified and non-scarified seeds were primed with 0.25, 0.5, 1, 2, 3, 4, 5 mM of gibberellic acid (GA 3 ), ascorbic acid (AsA) and salicylic acid (SA), respectively. Seeds were also hydroprimed and compared with unsoaked seeds (cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 25 publications
2
3
0
Order By: Relevance
“…Recovered seeds were insensitive to GA 4+7 in the light and only responded in the dark following extensive chilling in field soils. These observations with regard to temperature are consistent with those of Baskin & Baskin (); and similar to the low sensitivity to GA 3 seen previously (Sosnoskie & Cardina ; Yasin & Andreasen ).…”
Section: Discussionsupporting
confidence: 92%
“…Recovered seeds were insensitive to GA 4+7 in the light and only responded in the dark following extensive chilling in field soils. These observations with regard to temperature are consistent with those of Baskin & Baskin (); and similar to the low sensitivity to GA 3 seen previously (Sosnoskie & Cardina ; Yasin & Andreasen ).…”
Section: Discussionsupporting
confidence: 92%
“…In the laboratory, different populations from across a >2000 km latitudinal climate gradient showed no clines in germination but rather idiosyncratic responses to our treatments. Germination was enhanced by temperatures just above freezing as reported previously (Lhotska ) and did not require higher temperatures (Raghu & Post ) nor scarification (Sosnoskie & Cardina ; Yasin & Andreasen ). Onset of higher temperatures (>20 °C) effectively suppressed germination even of stratified seeds.…”
Section: Discussionsupporting
confidence: 81%
“…Similarly, SA, and especially BzA, concentrations grew during germination, which suggests that they are involved in embling development even though these compounds have been shown to exert inhibitory effects in some plant species, for example, those of the genera Alliaria ( Ribeiro et al, 2015 ). Yasin and Andreasen (2015) reported that increasing JA and SA concentrations are associated with the development of the vegetative axis in macaw palm seedlings.…”
Section: Discussionmentioning
confidence: 99%